Uncle Jack and the Emperor Penguins - Cadwallader, Jane (Italy ELI - Young Readers, 2009)
In this hilarious story you will learn something about the habits of the Emperor Penguins and follow Uncle Jack and the others in their race against time to help the penguins to the place where they lay their eggs.
Picture dictionary, games and activities.
Keywords: Adventure; Classroom activities; Elementary level; Language Learning